Test Case Generation from UML-Diagrams Using Genetic Algorithm - Kumar Sahoo, Rajesh; Derbali, Morched; Jerbi, Houssem; Van Thang, Doan; Pavan Kumar, P.; Sahoo, Sipra (Computers, materials & continua, 2021)
Software testing has been attracting a lot of attention for effective software development. In model driven approach, Unified Modelling Language (UML) is a conceptual modelling approach for obligations and other features of the system in a model-driven methodology. Specialized tools interpret these models into other software artifacts such as code, test data and documentation. The generation of test cases permits the appropriate test data to be determined that have the aptitude to ascertain the requirements. This paper focuses on optimizing the test data obtained from UML activity and state chart diagrams by using Basic Genetic Algorithm (BGA). For generating the test cases, both diagrams were converted into their corresponding intermediate graphical forms namely, Activity Diagram Graph (ADG) and State Chart Diagram Graph (SCDG). Then both graphs will be combined to form a single graph called, Activity State Chart Diagram Graph (ASCDG). Both graphs were then joined to create a single graph known as the Activity State Chart Diagram Graph (ASCDG). Next, the ASCDG will be optimized using BGA to generate the test data. A case study involving a withdrawal from the automated teller machine (ATM) of a bank was employed to demonstrate the approach. The approach successfully identified defects in various ATM functions such as messaging and operation.